Separation of E-waste Using Object Detection in IOT - Hishma T (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper introduces the integration of ultrasonic, infrared, and load sensors into smart e-waste management systems. We generally use ultrasonic sensors for monitoring waste fill levels in bins and containers. We can separate e-waste from other wastes through object detection using IoT. Object detection sensors are used in e-waste management systems. An IoT-enabled smart bin can use object detection to identify electronic equipment. IoT (Internet of Things), the between devices and the cloud and between the devices themselves, can separate metallic and plastic components using machine learning. Ultrasonic sensors can detect when a bin is full by sending signal waves to the sides of the bin and analyzing the values. These are the ideas that we would like to present in this paper.
Keywords: Object Detection; Internet of Things; Ultrasonic Sensor; Load Sensor